Impaired spermatogenesis caused by busulfan is partially ameliorated by treatment with conditioned medium of adipose tissue derived mesenchymal stem cells. (17th February 2022) - Abdollahifar, Mohammad-Amin; Azad, Nahid; Faraji Sani, Maryam; Raoofi, Amir; Abdi, Shabnam; Aliaghaei, Abbas; Abbaszadeh, Hojjat-Allah; Ebrahimi, Vahid; Fadaei Fathabadi, Fatemeh; Ghanimat, Faezeh; Movahedi, Maryam
ABSTRACT: Busulfan (BSU) is a chemotherapeutic drug that can cause subfertility or sterility in males. We investigated the effects of adipose tissue-derived mesenchymal stem cells (AT-MSC) conditioned medium (CM) (AT-MSC-CM) on histopathological and molecular characteristics of mouse testes exposed to BSU using stereology. We used adult male mice divided randomly into five groups: control, Dulbecco's modified Eagle's medium (DMEM), dimethyl sulfoxide (DMSO), BSU, and BSU + CM. Thirty-five days following BSU injection, sperm and testis tissues were harvested for stereological and molecular studies. The BSU group exhibited significantly reduced testis volume, interstitium and tubules compared to the other groups, although the volume of the testis remained unchanged for BSU and CM groups. The number of testis cells was reduced in the BSU group compared to the other groups. The CM group exhibited a significantly increased number of testis cells compared to the BSU group. Sperm count and motility, and length density of seminiferous tubules were increased in CM group compared to the BSU group. AT-MSC-CM exhibited ameliorative effects on histopathologic changes of mouse testes exposed to BSU.